Employee Resiliency After Termination Of Employment In The Covid-19 Pandemic In Sidoarjo - Raden Dimas Harsen (Universitas Airlangga, 2021)
The purpose of this research is to know the forms of resiliency to employees who are experiencing a terminationof employment at the Covid-19 pandemic that many companies termination employment as an impact of thecompany's operational restrictions in certain sectors by Government to reduce the transmission rate of Covid-19in Indonesia, including in Sidoarjo. This research used qualitative method. The subject in this study is wereemployees who has suffered a termination of employment by the company where they work in Sidoarjo. The datacollection techniques used in this study were through in-depth interviews with the topic of the employee's resilienceform post-termination work relationships in the Covid-19 pandemic, and the data analysis techniques in this studyusing case study approaches. The result of this study is (1) the subject is capable of overcoming pressure with anoptimistic attitude, (2) The subject can recover the situation so that the relationship with the closest person wellestablished,(3) The subject has good desire control so that it can withstand their current conditions without affecting theemotional condition. The conclusion of this research is the subject can accept situation of pressure very calmly,think positively, and also try hard to find a solution of the problems experienced by the subject after terminationof employment.